“Together in suffering, truly in trouble” – a study of cultural rituals in ultras supporters based on identity fusion theory - Chentianlei Su; Wangyang Li; Bin Liang; Peishan Li (Humanities & Social Sciences Communications)
Abstract Certain ritual elements in collective rituals are thought to trigger “identity fusion” among group members - an intrinsic feeling of being one with the group organization. This study aims to identify the key factors contributing to identity fusion in home and away game attendance. By analyzing the home and away game attendance and expedition behaviors of Chengdu Blades Ultras supporters (N = 206), we explored the associations between emotional intensity, cheering behavior without causal relation with win and lose, and inter-supporter synchronicity with identity fusion. The results are as follows: Study 1 showed that ~58.2% of the supporters in the sample exhibited a high degree of identity fusion characteristics. Study 2 showed that opaque causal behaviors (p = 0.002), synchronous behaviors (p < 0.001), and strong emotional responses (p = 0.033) significantly enhanced fusion in the context of home game attendance. Study 3 found that only opaque causal (p < 0.001) and synchronous behaviors (p < 0.001) were consistent with the hypothesis in the away expedition context. Therefore, we used a specific match in which Chengdu drew 1–1 away from Qingdao as the context for our Study 4 with 69 supporters participating in this expedition. We found that emotional intensity (p = 0.033), causal opacity (p = 0.002), and synchronized behavior (p < 0.001) significantly and positively predicted identity fusion in the context of the decisive away match. These findings further confirm the significant role of ritual elements in predicting identity fusion and provide new perspectives for understanding the social impact of collective rituals.